Nano-SiO2 and PVA Fiber Synergistically Strengthened Concrete to Optimize the Antifreeze, Antipermeability, and Anticorrosion Performance of Roads - Li Tang (Advances in Materials Science and Engineering)
As a modified material, nano-SiO2 can be compounded with many high molecular polymer resins to improve the performance of the polymer and be used as a concrete filler. PVA is a kind of synthetic fiber made of high-quality polyvinyl alcohol with a high degree of polymerization and processed by specific advanced technology. This research mainly discusses the optimization of the antifreeze, antipermeability, and anticorrosion performance of the concrete reinforced by nano-SiO2 and PVA fiber synergistically. In this paper, nanosilica PVA fiber-modified concrete was synthesized. Through compressive strength test, split tensile strength test, rapid freeze-thaw test, and microstructure test (X-ray diffraction and scanning electron microscope), this paper also analyzed the modification effect of PVA fiber concrete in different blends and the corresponding mechanism of nanoparticles. The instrument model of the scanning electron microscope used is S-4700; the manufacturer is Hitachi, a Japanese company; and the test voltage is 20 kV. Before the test, the hydrogel was placed in a freeze-drying oven at −40°C for 48 hours to remove water. Then, we put the sample in liquid nitrogen and break. The morphology of the cross-section was observed by SEM, and the microscopic morphology changes brought by different amounts of MTMS to the hydrogel were analyzed. After the test piece is immersed in water to reach a saturated state, we check the appearance size of the test piece, wipe the surface of the test piece clean with a rag, weigh the unfreeze-thaw test piece, then measure the ultrasonic wave speed of the test piece with a nondestructive testing instrument, and do good record. After every 25 freeze-thaw cycles, we measure the mass and relative dynamic elastic modulus of each group of specimens, make corresponding records, then put them into the freeze-thaw box, and add clean water as the freeze-thaw medium to continue the test. The average initial crack load of the three specimens of WW3 is increased by 52% compared with that of the specimens of WW1, and the load of WW4 is increased by 77%. This research helps promote the application of concrete on roads.